(untitled) (Cambridge, 2001)
Why are females rarely antisocial and males antisocial so often? This is one of the key questions addressed in a fresh approach to sex differences in the causes, course and consequences of antisocial behavior. A multidisciplinary team of authors present all-new findings from the landmark Dunedin Longitudinal Study and also provide new insights into such topics as the importance of puberty, diagnostic issues in psychiatry, the problem of domestic violence and the intergenerational transmission of antisocial behavior.
Keywords: Rối loạn hành vi ở tuổi vị thành niên,Rối loạn nhân cách chống đối xã hội,Tình trạng vị thành niên phạm tội,Conduct disorders in adolescence,Antisocial personality disorders,Juvenile delinquency; Khác biệt giới tính,Khác biệt giới tính,Khác biệt giới tính,Sex differences,Sex differences,Sex differences